2023
DOI: 10.1007/s10814-023-09186-y
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Research in the Canary Islands: Island Archaeology off Africa’s Atlantic Coast

Abstract: Island archaeology is a well-established field within the wider discipline, but African contributions to it remain scarce. The Canary Islands are unusual in the broader African context for their relatively long history of occupation (~2000 years) and the intensity with which archaeological research has been, and is, undertaken there. Much of that research, however, has focused on specifically Canarian issues, including efforts to demonstrate connections between the islands’ initial settlement and the Classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 159 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…The arrival time of human and livestock on the Canary Islands is still debated, revealing a paradoxical timeline spanning almost 1000 years [ 30 ]. Indeed, several authors have suggested an early colonization during the 1st millennium BC, when the Amazigh peoples started occupying the Archipelago, while others argue for a more recent arrival dating back to the Roman period [ 1 , 2 , 31 , 32 ]. The Imazighen ethnic and linguistic family extends through Morocco, Algeria, Tunisia, Libya, and Mauritania as well as small pockets of Mali, Niger, and Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival time of human and livestock on the Canary Islands is still debated, revealing a paradoxical timeline spanning almost 1000 years [ 30 ]. Indeed, several authors have suggested an early colonization during the 1st millennium BC, when the Amazigh peoples started occupying the Archipelago, while others argue for a more recent arrival dating back to the Roman period [ 1 , 2 , 31 , 32 ]. The Imazighen ethnic and linguistic family extends through Morocco, Algeria, Tunisia, Libya, and Mauritania as well as small pockets of Mali, Niger, and Egypt.…”
Section: Discussionmentioning
confidence: 99%